EFFECT OF DELAYED CELL PROCESSING AND CRYOPRESERVATION ON IMMUNOPHENOTYPING IN MULTICENTER POPULATION STUDIES - Thyagarajan, Bharat (J Immunol Methods, 2018)
Variability induced by delayed cell processing and cell cryopreservation presents unique challenges for immunophenotyping in large population studies. We conducted a pilot study to evaluate the effect of delayed cell processing and cryopreservation on cell percentages obtained by immunophenotyping. We collected blood from 20 volunteers and compared the effect of (a) delayed cell processing up to 72 hours (b) cryopreservation and (c) the combined effect of delayed cell processing and cryopreservation on immunophenotyping of 31 cell subsets that included several subsets of T, B, Natural Killer (NK) cells, monocytes and dendritic cells using both whole blood collected in EDTA tubes and peripheral blood mononuclear cells collected in CPT tubes. We found the delayed cell processing up to 72 hours or cryopreservation alone did not significantly affect the percentages T cells, dendritic cells or monocytes but significantly increased the percentage of B cells and NK cells (p for trend ≤0.01) but. However combination of delayed cell processing up to 72 hours and cryopreservation significantly increased the percentage of T cells as compared to cells processed immediately (p for trend <0.0001) while a delayed cell processing followed by cryopreservation decreased the percentage of NK cells (p for trend <0.0001). Total B-cells increased significantly with a 24-48 hour delay in cell processing and cryopreservation but not at 72 hours. The percentages of monocytes and dendritic cells remained unaffected by the combination of delayed cell processing and cryopreservation. These findings suggest that immunophenotyping of several immune cell subsets can be successfully implemented in large population studies as long as blood is processed within 48 hours of biospecimen collection though some cell subsets may be more susceptible to a combination of delayed cell processing and cryopreservation.